The measurement of menstrual symptoms: Factor structure of the menstrual symptom questionnaire in adolescent girls - NEGRIFF, SONYA (J Health Psychol, 2009)
This study examined the factor structure of the Menstrual Symptom Questionnaire (MSQ) in a sample of 210 adolescent girls (11–17 years). Such an examination has not been carried out with an adolescent sample. In addition, the definitions of menstrual disorders have evolved since the creation of the MSQ. Exploratory factor analysis supported a three factor structure indicating abdominal pain, negative affect/somatic complaints, and back pain. Partial correlations indicated all three MSQ factors were correlated with depressive symptoms, but only the negative affect factor was correlated with trait anxiety. Future research should explore potential associations in multiple areas of functioning as menstrual symptoms may alter healthy developmental processes during adolescence.